Prp19 Is an Independent Prognostic Marker and Promotes Neuroblastoma Metastasis by Regulating the Hippo-YAP Signaling Pathway - Cai, Yuanxia; Chen, Kai; Cheng, Cheng; Xu, Yonghu; Cheng, Qianqian; Xu, Guofeng; Wu, Yeming; Wu, Zhixiang (Frontiers in Oncology, 2020)
Pre-mRNA processing factor 19(Prp19) was previously reported to involve in tumor progression. However, the Prp19 expression and functions remain elusive in neuroblastoma. Here we aim to identify the functions and mechanisms of Prp19 in neuroblastoma. Neuroblastic tumor tissue microarrays and two independent validation datasets indicated that Prp19 was associated with high-risk markers, bone marrow metastasis and served as a prognostic marker for worse clinical outcome in neuroblastoma. Gain- and loss-of-expression assays revealed that Prp19 promoted invasion, migration and epithelial–mesenchymal transition (EMT) of neuroblastoma cells in vitro. Bioinformatics analysis of RNA-seq data showed that the expressions of YAP and its downstream genes were significantly inhibited after downregulation of Prp19. Prp19 and YAP expression in metastatic lymph nodes was higher than in situ neuroblastoma tissue. Further experiments showed that Prp19 regulated YAP expression and consequently infect cell invasion, migration and EMT in neuroblastoma by pre-mRNA splicing of YAP. In conclusion, our findings provide the first evidence that Prp19 is a potential therapeutic target and prognostic biomarker for patients with neuroblastoma.